The Racial Prejudice Toward The Black In America As Reflected In James Mcbride The Color Of Water - Sanopa Sanopa (Fakultas Sastra Universitas Ekasakti, 2017)
This thesis discusses the issue of racial prejudice in America described in the novel The Color of Water written by James Mcbride. This analysis focuses on how blacks are perceived differently by other races in America such as whites. In this study, the authors analyzed three problems, the first why race prejudice occurred in America. How racial prejudices against blacks as uneducated people, how racial prejudice against blacks as criminal. In analyzing the literary work, the author uses postcolonial theory, it is this theory that allows us to see how the colonial influence both during colonization lasted, before, and after the colonialization ended like today. This theory has a very important meaning, The hidden problems contained behind the facts that have occurred, and very in accordance with the problems contained in the novel the color of water. In this study, the authors found a 1). bad relationship between the minority and the majority in the United States really happened. 2). Minorities such as blacks get white prejudices. This disharmony of relationships has some impact on the minority itself, the impact of which can be seen from how the quality of life of these minorities. 3). Another consequence of the harmony of the relationship is the emergence of awareness and motivation in the minority to be equal to the majority.